2021
DOI: 10.3390/ma14112760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Lathe Waste Addition on the Mechanical and Thermal Properties of Concrete

Abstract: The amount of steel chips generated by lathes and CNC machines is 1200 million tons per year, and they are difficult to recycle. The effect of adding steel chips without pre-cleaning (covered with production lubricants and cooling oils) on the properties of concrete was investigated. Steel waste was added as a replacement for fine aggregate in the amounts of 5%, 10% and 15% of the cement weight, which correspond with 1.1%, 2.2% and 3.3% mass of all ingredients and 0.33%, 0.66% and 0.99% volume of concrete mix,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…Moreover, according to the EOTA [ 2 ] and Eurocode 2 [ 3 ], fastenings made in fiber-reinforced concrete elements were designed and implemented as typical concrete substrates. This does not correspond to the actual operating conditions of fasteners, which are often installed in elements made of fiber-reinforced concrete [ 10 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. An example is fiber-reinforced concrete floors [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to the EOTA [ 2 ] and Eurocode 2 [ 3 ], fastenings made in fiber-reinforced concrete elements were designed and implemented as typical concrete substrates. This does not correspond to the actual operating conditions of fasteners, which are often installed in elements made of fiber-reinforced concrete [ 10 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. An example is fiber-reinforced concrete floors [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A fabricação de aço está intimamente ligada à produção de resíduos de usinagem, um torno pode gerar aproximadamente de 3 a 4 quilos desse resíduo por dia de trabalho. A título de exemplo, de acordo com o Investment Company Institute, a produção total desse tipo de resíduo já atingiu cerca de 1.200 milhões de toneladas anualmente [2].…”
Section: Introductionunclassified
“…Waste materials can also be used as fibers in concrete and cement composites [ 15 ], increasing their strength properties. As Małek et al showed in [ 16 ], the addition of metal lathes waste from postproduction of mechanical components increases the mechanical properties of concrete. Sobuz et al [ 17 ] emphasized the advisability of producing UHPCs with the use of commonly available materials and without special curing conditions.…”
Section: Introductionmentioning
confidence: 99%